Hepatoid adenocarcinoma of the lung mimicking metastatic hepatocellular carcinoma - Yu Miyama; Takeshi Fujii; Kyoko Murase; Hisashi Takaya; Fukuo Kondo (University of São Paulo, 2021)
Hepatoid adenocarcinoma of the lung is a rare subtype of lung cancer. We report a case of a metastatic hepatoid adenocarcinoma of the lung with aggressive behavior, including biopsy and autopsy findings. The pulmonary tumors showed features indistinguishable from hepatocellular carcinoma and were diffusely positive for Hepatocyte Paraffin 1.